Pengaruh Persepsi dan Preferensi Tamu Terhadap Keputusan Menginap di Hotel Syariah Kota Bandung - Ita Karnita; Lu’luwatin Rosdiana Aprilia (STIEPAR YAPARI Bandung, 2021)
This study aims to analyze how preceptions, preference and stay decision of syariah hotel guest in northern part of Bandung ((Hotel Noor, Hotel Narapati dan Hotel Darul Jannah). The method used in this research is quantitative methods. The population in this study were guest of syariah hotel in northern part of Bandung ((Hotel Noor, Hotel Narapati dan Hotel Darul Jannah). Sampling technique used in this method, while for calculating the amount of sample size using formula slovin. The number of respondent are 150 people. Probability sampling used as a technique sampling. Path analysis was used to analyze the result in this research. The result of this research showed thatstay decision influenced by the perception and preference. Perceptions influenced stay decision of syariah hotel guest more than preference variable.. The limited conditions of perceptions and preference will be impact to the low stay decision of guest. . In addition the research also showed that perceptions and preference significantly influence stay decision.